Study of Two Farmer-Led Extension Approaches in Uttarakhand Hills - S.R.K. Singh, S.K. Pandey, A.K. Dixit, R.S. Negi, S.S. Gautam (Indian Journal of Extension Education, 2022)
Agricultural extension is playing untiringly role in uplifting the quality of life of the farmers and farm women in hills. Different extension approaches are being used in different location and considered as appropriate in that location. This study was conducted on the beneficiary of the Farmer to farmer extension (FFE) and Farmer field school (FFS). Results shown that both the approaches had its own objective and implementation process and made impact on the hill farmers differently. FFE advice was concentrated on making farmers’ group, seed replacement and low external input use, whereas, FFS advised on seed treatment, scientific nursery raising, vermin-composting and judicious use of pesticides, etc. Both the approaches advocated for green agriculture in hills. Analysis showed that there were no significant differences between the two approaches in regard to gender, level of education, and leadership position. Regarding extension methods deployed, FFE used more mass approaches, whereas, FFS used group approach. FFE were the monthly interaction meetings in which scientists and extension agents meet with the farmers. In FFS, the main source of technical packages was the field training provided at the onset of the crop season in the selected farmers plots. Both the approaches proved effective for the dissemination of the technical information but FFS proved more appropriate and effective in extending the skill training to the farmers due to its field training during the crop season. Thus, this study gives a roadmap for the change agents for making suitable extension strategy.